"Analysis of the Technological Sketch of the Shaft, Developed using the Program Corel Draw" - Shukhratkizi, Akramova Dilafruz; Abdurashidugli, Fatkhullaev Alisher (International Journal of Human Computing Studies, 2022)
At first sight, the "Shaft" part would seem to have a simple structure in relation to other machine parts. But, sometimes Shafts are found with a very complex design. Their complexity is explained by the presence in their design of such surfaces as: grooves, chamfers, threaded surfaces, flats, beads, grooves, groove holes, fillets, etc., the images of which are shown below.